Compling a Database of Agricultural Potential of Nagari Air Manggis Selatan Through Crowdsourching-Based Participatory Mapping - Muhammad Ismail; Wikan Jaya Prihantarto; Bayu Wijayanto; Sari Nova; Elisa Maiyenti; Hendry Frananda; Yusra Aprila Putri; Mutiara Amelia Putri (JPG (Jurnal Pendidikan Geografi), 2026)
Geospatial data and information can be used for potential of villages. Apart from that, village must have data also on the potential of its main area for sectors that are dominant and support the local economy. Based on these problems, it is very important to pay attention to the provision of a spatial database in the form of the potential of the dominant productive sector. Nagari Air Manggis Selatan, Lubuk Sikaping District, Pasaman Regency has large resource potential, one of which is agriculture. However, until now there is no representative data regarding the spatial distribution and extent of agricultural land in the village. Currently, technology is developing rapidly, everyone to contribute voluntarily. This has the potential to be developed to increase technological independence, information and regional development. The aim of this research is to provide assistance to the community in carrying out data collection, building a database, and publishing agricultural potential data independently based on crowdsourching. The activity began with socialization and a focus group discussion to formulate relevant agricultural potential information. Assistance to the community is provided to map agricultural land in a participatory. Utilization of digital forms to update agricultural potential data is also carried out. The collected data is managed in a cloud database and displayed in Web-GIS